2022
DOI: 10.1111/ijfs.15564
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying properties of pea protein/guar gum conjugates and mayonnaise application

Abstract: Modified plant protein may be used as a healthy and more functional emulsifier in food products. The objective of this study was to evaluate the emulsifying properties of functionally enhanced pea protein (i.e. pea protein conjugated with guar gum, G-PPI) and its potential application to mayonnaise, compared with unmodified pea protein. Emulsions containing G-PPI were prepared at different pH, salt concentrations, protein concentrations and oil/water ratios. Mayonnaise samples were prepared using the pea prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Usually, mayonnaise prepared with proteins that have excellent emulsifying properties presents more compact and uniform droplets, which can prevent droplets from flocculation or coalescence by increasing steric repulsion. Conversely, mayonnaise prepared with proteins that have poor emulsifying properties shows oil droplets with flocculation (Shen, Babu, et al., 2022). MBPs had lower emulsifying properties than other leguminous proteins, such as cowpea, soybean, and pea proteins, at pH 3.0, 7.0, and 9.0, with the EAI values of all proteins at 8.70–9.62, 9.10–10.33, and 9.59–10.16 m 2 /g, respectively, and ESI values of 110–460, 250–465, and 500–2800 min, respectively (Ge et al., 2021).…”
Section: Extraction Methods and Ingredients Characteristics Of Mbpmentioning
confidence: 99%
“…Usually, mayonnaise prepared with proteins that have excellent emulsifying properties presents more compact and uniform droplets, which can prevent droplets from flocculation or coalescence by increasing steric repulsion. Conversely, mayonnaise prepared with proteins that have poor emulsifying properties shows oil droplets with flocculation (Shen, Babu, et al., 2022). MBPs had lower emulsifying properties than other leguminous proteins, such as cowpea, soybean, and pea proteins, at pH 3.0, 7.0, and 9.0, with the EAI values of all proteins at 8.70–9.62, 9.10–10.33, and 9.59–10.16 m 2 /g, respectively, and ESI values of 110–460, 250–465, and 500–2800 min, respectively (Ge et al., 2021).…”
Section: Extraction Methods and Ingredients Characteristics Of Mbpmentioning
confidence: 99%
“…Stabilizer, thickener, gluten-free noodles, emulsifier, reducing oil uptake during fry [150] Beverage Industry Thickener, stabilizer, dietary fiber [151] Dairy Products…”
Section: Improving Texturesmentioning
confidence: 99%
“…The results showed that GG strongly correlated with the textural properties over the other parameters (Wang et al, 2016 ). Shen et al ( 2022 ) supplemented mayonnaise samples with pea protein and GG (G‐PPI), and then they found that the stability of G‐PPI emulsions had significantly increased. Also, treated samples exhibited excellent emulsifying and rheological properties (Shen et al, 2022 ).…”
Section: Applications Of Guar Gum In the Food Industrymentioning
confidence: 99%